Assessment of Outcomes in Surgically Staged I/II Endometrial Adenocarcinoma Patients Treated With Postoperative Vaginal Vault Radiotherapy Only. Issue 8 (1st October 2010) - Eiriksson, Lua; Cuartero, Julie; Steed, Helen; Pearcey, Robert; Capstick, Valerie; Schepansky, Alexandra; Faught, Wylam; Dundas, George
Abstract : Objective: To examine the efficacy of vaginal vault radiotherapy as adjuvant treatment for patients with high-grade, stage I/II endometrial adenocarcinoma who have been surgically staged. Methods: A retrospective chart review of 77 women between 1995 and 2006 with high-grade surgically staged I and II endometrial adenocarcinoma, who were treated with postoperative vaginal vault radiotherapy alone, was performed. The primary study end points were recurrence risk and sites of recurrence. The secondary end points were disease-free and overall survival. Kaplan-Meier estimates were calculated for overall and disease-free survival. Results: Seventy-seven women were identified and met inclusion criteria. Sixty-seven (87%) had grade 3 histologic features on final pathologic report. Forty-two patients (55%) were classified as stage IB, having superficial myometrial invasion; 21 (27%) were stage IC, with deep invasion; and 6 (8%) were stage II, involving the cervix. The median follow-up was 80 months (6.6 years). There were 10 recurrences (13.0%), of which 3 were local: 1 involving the vaginal apex; 1, the lower vagina and pelvic sidewall; and 1, the lower vagina. The 5-year recurrence risk was 11.2% and the 5-year survival probability 88.9%. Conclusions: It seems that for this cohort of 77 patients with surgically staged I and II grade 3 endometrial adenocarcinoma, adjuvant vaginal vault radiotherapy alone leads to acceptable recurrence rates and survival while minimizing morbidity.